Hydrogen impact on the shrinkage behaviors of wustite packed beds above 900 °C. (26th July 2019) - Ma, Kaihui; Xu, Jian; Deng, Junyi; Kou, Mingyin; Wen, Liangying
Abstract: The steel industry is facing increasing pressure and challenges from the environment in recent years. The urgent utilization of clean energy not only reduces greenhouse gas emissions, but also promotes future innovations in blast furnace iron making technology. Hydrogen (H2 ) energy is considered to be one of the most promising alternatives to carbon-based fossil energy for the reduction of iron oxides. Therefore, the gaseous reduction of iron oxides by H2 has been intensively studied for decades. However, the impact of H2 on the shrinkage behavior of iron oxide packed beds above 900 °C has rarely been studied, and the interaction between H2 and carbon monoxide (CO) in the shrinking process is not fully understood. Therefore, this study uses H2, CO and H2 +CO mixture gas for the well-designed high temperature experiments of wustite (FeO) packed beds. The results show that H2 protects the coke from further damage in the packed bed at 900–1000 °C, and the corresponding shrinkage rate (SR) decreases from 0.31%/°C for CO case to 0.16%/°C. Meanwhile, when the temperature exceeds 1350 °C, the packed bed under the CO atmosphere accelerates shrinkage due to the melting and dripping of the metallic iron after carbonization. By contrast, when CO is replaced by H2, the carbonization process is controlled by the solid state diffusion of coke carbon rather than the reverse Boudouard reaction. As a result, the lower carbonization efficiency not only increases the transition temperature by up to 100 °C, but also reduces the weight of the melted hot metal by one third, which significantly improves the bed permeability. Highlights: H2 reduces the shrinkage rate by protecting coke from further damage at 900–1000 °C. H2 postpones the transition temperature for re-accelerating shrinkage to 1450 °C. H2 reduces the weight of melted hot metal after carbonization by one third. H2 significantly improves the bed permeability in the shrinking process.